Accidental Intravenous Administration of Simethicone in a 4-Year-Old Patient: A Case Report - Lozovskytė, Agnė; Laubner Sakalauskienė, Gabija; Badaras, Robertas (Acta medica Lituanica, 2024)
Simethicone is an antiflatulent medication exclusively administered orally, thus its systemic effects remain unknown. We present a case of an inadvertent intravenous administration of simethicone to a 4-year-old patient, precipitating respiratory difficulty, cyanosis, and altered mental status. The patient’s condition improved rapidly with appropriate interventions, leading to discharge in a fully recovered state. To date, only one documented instance of intravenous simethicone administration exists in medical literature.
Keywords: Simethicone; Accidental intravenous administration; Respiratory distress ir pediatric case; Medication error